Parque das Neblinas: an important reserve for Atlantic Forest bird conservation in Southeast Brazil - Fabio Schunck; Bruno Rennó; Fernando I. de Godoy; Gérard Baudet; Kleber E. Rodrigues; Tomas Sigrist; Marcelo Bokermann (Zoologia (Curitiba))
ABSTRACT The Atlantic Forest has one of the richest avifaunas in the world, with endemic, migratory and endangered taxa. However, some of the ornithological knowledge produced there has yet to be organized and published, hindering effective conservation actions. For example, a study concluded in 2005 documented 213 species for Parque das Neblinas (PN), a private reserve located in the Serra do Mar in the state of São Paulo, Brazil, but there has been no update since. We retrieved, organized, and technically evaluated ornithological data produced for PN over the last 20 years, including that from articles, online platforms, occasional lists and a systematic inventory logging 250 field hours. Data consolidation resulted in 293 bird species for PN, including 88 endemic and nine threatened with extinction. Two-hundred and fifty-seven species were recorded by different researchers and bird observers while 141 were recorded by the field inventory, which added 24 species to the total list, showing great potential for new research. The PN bird community is typical of the São Paulo plateau, with the occurrence of species from coastal lowlands as well as drier areas in the interior, and represents an important area for the conservation of Atlantic Forest birds that is also suitable for bird observation and photography.